The Struggle Never Ends (The Reflection on the History of Struggle between Socio-Political Groups in the Creation of Painting) - M. Agus Burhan; Miftakhul Munir; Agatha Christi (Journal of Urban Society's Arts, 2022)
This artistic research aims for the creation of contemporary painting. State of art issues of art creation consists of paintings, socio-political, social functions, and visual symbols. The creation goals are to create painting from the ideas of creation and aesthetics visual form, departing from socio-political history condition in the struggle among mass organizations and politic organizations in Indonesia. By utilizing practice-based research method, the researcher is united with the object being worked in an in and through appreciation, must also refer to published creation method, thus that it is not subjective and the explanation is detailed. David Campbell’s creation method is used as the reference, i.e., Preparation, concentration, incubation, illumination, and verification-production. The study results and art design are contemporary painting “Pertarungan tak Kunjung Usai” (The Struggle Never Ends). It portrays the reflection of ideology struggle and socio-political outlook of figures or among community groups. Subject matter shows two figures group who facing and opposing each other with allegory or symbol attributes, such as weaponries, normative books, bulls, and garudas. The setting is on a ruins or ship deck wreckage. The painting is shown in decorative-expressive style, within contemporary aesthetic artistic images. Penelitian artistik ini bertujuan untuk penciptaan karya seni lukis kontemporer. State of art permasalahan penciptaan karya meliputi seni lukis, sosial-politik, fungsi sosial, dan simbol visual. Tujuan penciptaannya menciptakan lukisan dari ide penciptaan dan bentuk visual yang estetik, dari fenomena kondisi sejarah sosial politik dalam pertarungan ormas dan orpol yang ada di Indonesia. Metodenya practice based research, peneliti menyatu dengan objek yang dikerjakan dalam penghayatan secara timbal balik (in and through), juga harus merujuk metode penciptaan terpublikasi, sehingga tidak subjektif dan pemaparannya rinci. Metode penciptaan David Campbell digunakan sebagai rujukan, yaitu preparation, concentration, incubation, illumination, verification-production. Hasil penelitian dan perancangan karya ini adalah karya seni lukis kontemporer "Pertarungan Tak Kunjung Usai". Menggambarkan refleksi pertarungan ideologi dan pandangan sosial politik dari figur-figur atau antarkelompok masyarakat. Subject matter menampilkan dua kelompok figur-figur yang berhadapan dan saling bertentangan dengan masing-masing atribut alegori atau simbolnya, seperti senjata, kitab normatif, banteng, dan garuda. Setingnya ada dalam reruntuhan bangunan atau potongan geladak kapal. Lukisan ini ditampilkan dalam gaya dekoratif ekspresif, dalam citra artistik estetika kontemporer.